2008
DOI: 10.1017/s1751731108002802
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation and its relationship to physical meat quality attributes of beef from Nguni and Bonsmara steers raised on natural pasture

Abstract: The current study compared sensory characteristics and their relationships with physical meat characteristics of beef from Nguni and Bonsmara steers. Nguni beef was more (P , 0.05) tender than Bonsmara beef after ageing for 2 and 21 days, and had higher (P , 0.05) intramuscular fat (IMF; 1.12%) than Bonsmara beef (1.07%). Nguni beef had higher (P , 0.05) sensory scores than Bonsmara beef after ageing for 2 days. There were no (P . 0.05) relationships between IMF and sensory characteristics. Aroma intensity, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
5
20
0
Order By: Relevance
“…This therefore support the previous observations that amount of connective tissues alone is insufficient to explain tenderness of goat meat (Muchenje et al, 2008b). Factors such as cooking method, fat content, muscle fibre composition, electrical stimulation and aging regime also can affect tenderness (Dzudie et al, 2000;Muchenje et al, 2008aMuchenje et al, , 2009c.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This therefore support the previous observations that amount of connective tissues alone is insufficient to explain tenderness of goat meat (Muchenje et al, 2008b). Factors such as cooking method, fat content, muscle fibre composition, electrical stimulation and aging regime also can affect tenderness (Dzudie et al, 2000;Muchenje et al, 2008aMuchenje et al, , 2009c.…”
Section: Resultssupporting
confidence: 89%
“…However, first bite scores showed that the meat mixed with vegetables and the intestines were more soft and tender than the cooked plain and roasted (P < 0.05). Ideally, meat quality levels combine the capacity to retain high nutritional value in the cooked form and to excel in functional roles such as flavor development, tenderness and juiciness of the cooked product among other roles (Muchenje et al, 2008a(Muchenje et al, , 2009c. Muscle fibre and overall tenderness, amount of connective tissue, overall flavour intensity and relevant atypical flavor were significantly (P < 0.05) affected by cooking method.…”
Section: Resultsmentioning
confidence: 99%
“…These farmers keep indigenous chickens, and to a large extent, crossbred chickens produced from the indiscriminate crossbreeding of imported fast growing birds and the local hens. Due to the increasing demand for natural or organic meat that has been produced with minimal use of additives and chemicals, the relevance of indigenous chickens, which can be produced without any supplementary feeding and are highly tolerant of local diseases and parasites (Muchenje, Dzama, Chimonyo, Strydom, & Raats, 2008a), has increased. To promote the production of indigenous chickens, even on a large scale, information on the carcass characteristics, weight of organs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is because meat is the end product in beef production (Gebresenbet et al, 2011;Northen, 2011). However, animals may not produce the same levels of carcass and intramuscular fat, colour, pH and tenderness because of differences in genotype, age, sex, type of production systems, pre-slaughter conditions and post-mortem changes during meat processing and storage (Muchenje et al, 2008;Sentandreu & Sentandreu, 2011). The slaughter environments and processing of meat affect the quality of meat.…”
Section: Structural Changes In Meatmentioning
confidence: 99%